Mangifera indica L., by-products, and mangiferin on cardio-metabolic and other health conditions: a systematic review - DUARTE, Lidiane Gonsalves (130, 2024)
Mango and its by-products have traditional medicinal uses. They contain diverse bioactive compounds offering numerous health benefits, including cardioprotective and metabolic properties. This study aimed to explore the impact of mango fruit and its by-products on human health, emphasizing its metabolic syndrome components. PUBMED, EMBASE, COCHRANE, and GOOGLE SCHOLAR were searched following PRISMA guidelines, and the COCHRANE handbook was utilized to assess bias risks. In vivo and in vitro studies have shown several benefits of mango and its by-products. For this systematic review, 13 studies met the inclusion criteria. The collective findings indicated that the utilization of mango in various forms—ranging from fresh mango slices and mango puree to mango by-products, mango leaf extract, fruit powder, and mangiferin—yielded many favorable effects. These encompassed enhancements in glycemic control and improvements in plasma lipid profiles. Additionally, mango reduces food intake, elevates mood scores, augments physical performance during exercise, improves endothelial function, and decreases the incidence of respiratory tract infections. Utilizing mango by-products supports the demand for healthier products. This approach also aids in environmental conservation. Furthermore, the development of mango-derived nanomedicines aligns with sustainable goals and offers innovative solutions for healthcare challenges whilst being environmentally conscious.

RESUMO: A manga e seus subprodutos têm usos medicinais tradicionais. Eles contêm diversos compostos bioativos que oferecem inúmeros benefícios à saúde, incluindo propriedades cardioprotetoras e metabólicas. Este estudo teve como objetivo explorar o impacto da manga e seus subprodutos na saúde humana, enfatizando seus componentes da síndrome metabólica. PUBMED, EMBASE, COCHRANE e GOOGLE SCHOLAR foram pesquisados ​​seguindo as diretrizes PRISMA, e o manual COCHRANE foi utilizado para avaliar riscos de viés. Estudos in vivo e in vitro demonstraram diversos benefícios da manga e seus subprodutos. Para esta revisão sistemática, 13 estudos preencheram os critérios de inclusão. As descobertas coletivas indicaram que a utilização da manga em diversas formas – desde fatias de manga fresca e purê de manga até subprodutos de manga, extrato de folha de manga, fruta em pó e mangiferina – produziu muitos efeitos favoráveis. Estes incluíram melhorias no controle glicêmico e melhorias nos perfis lipídicos plasmáticos. Além disso, a manga reduz a ingestão de alimentos, eleva os índices de humor, aumenta o desempenho físico durante o exercício, melhora a função endotelial e diminui a incidência de infecções do trato respiratório. A utilização de subprodutos da manga apoia a demanda por produtos mais saudáveis. Essa abordagem também auxilia na conservação ambiental. Além disso, o desenvolvimento de nanomedicamentos derivados da manga alinha-se com objetivos sustentáveis ​​e oferece soluções inovadoras para desafios de saúde, ao mesmo tempo que é ambientalmente consciente.
Mangifera indica L., subprodutos e mangiferina em condições cardiometabólicas e outras condições de saúde: uma revisão sistemática
Artigo científico válido como TCC. Publicado em: Life 2023, 13, 2270. https://doi.org/10.3390/life13122270
Keywords: Manga; Compostos bioativos; Antioxidantes; Produção Alimentícia